Catalogue of the Order Amphipoda from Brazil (Crustacea, Peracarida): Suborders Amphilochidea, Senticaudata and Order Ingolfiellida - Serejo, C.s.; Siqueira, S.g.l. (Zootaxa, 2018)
This catalog documents 303 species within 142 genera and 56 families distributed in the suborders Amphilochidea, Senticaudata and order Ingolfiellida that have been described or reported for the Brazilian coast and continent. Data for these species such as type material, type locality, geographic and bathymetric distribution, ecological notes and remarks, when pertinent, was given. From these, 268 species (~ 90%) are benthonic, marine and/or estuarine occurring from a diverse type of substrates as sediment, algae, sponges, cnidarians, ascideans, mangrove roots, fouling habitats, coral rubble, rodolith banks, etc. In terms of bathymetry, there are 214 species (~ 80%) reported for the Brazilian continental shelf (0–200 m) and 60 (~20%) for the deep sea zone (> 200 m, 50% from the Campos Basin area). There are 35 non-marine amphipods reported from Brazil. Hyalella is the restricted and dominant epigean group and is represented by 22 species, including some hypogean and cave species. Cave dwellers includes 15 species within 6 genera as: Hyalella (5); Megagidiella (1); Potiberaba (1); Spelaeogammarus (7), and Seborgia (1). Among the Bogidiellidae, Bogidiella neotropica Ruffo, 1952 and Marigidiella brasiliensis (Siewing, 1953) are hypogean, but not from caves. The former is the only amphipod species recorded from the Brazilian Amazon Biome, within the Tapajós River, Pará and the latter are found in marine coastal groundwater of Bahia and São Paulo. Considering the landhoppers (truly terrestrial), only two introduced species, Talitroides alluaudi (Chevreux, 1896) and Talitroides topitotum (Burt, 1934) have been found in the Atlantic forest biome, urban parks and sylviculture plantations from the southeast and south of Brazil. Moreover, several amphipod records for Brazil were noticed to be dubious or misidentifications and are listed in a table with pertinent literature.